2020
DOI: 10.1016/j.isci.2020.101398
|View full text |Cite
|
Sign up to set email alerts
|

SenX3-RegX3, an Important Two-Component System, Regulates Strain Growth and Butenyl-spinosyn Biosynthesis in Saccharopolyspora pogona

Abstract: Summary Butenyl-spinosyn produced by Saccharopolyspora pogona exhibits strong insecticidal activity and a broad pesticidal spectrum. Currently, important functional genes involved in butenyl-spinosyn biosynthesis remain unknown, which leads to difficulty in efficient understanding of its regulatory mechanism and improving its production by metabolic engineering. Here, we present data supporting a role of the SenX3-RegX3 system in regulating the butenyl-spinosyn biosynthesis. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 42 publications
(55 reference statements)
1
20
0
Order By: Relevance
“…Although much progress has been made in understanding the butenyl-spinosyn biosynthetic pathway, little is known about the regulation of butenyl-spinosyn biosynthesis. To date, only a few regulators have been identified as being involved in the regulation of butenyl-spinosyn production in S. pogona , including the SenX3/RegX3 system, Sp1418, Sp13016, SP_1288 and an AfsR regulatory factor [ 7 11 ]. A better understanding of the regulatory mechanisms of butenyl-spinosyn biosynthesis will provide important insights for strain improvement by metabolic engineering.…”
Section: Introductionmentioning
confidence: 99%
“…Although much progress has been made in understanding the butenyl-spinosyn biosynthetic pathway, little is known about the regulation of butenyl-spinosyn biosynthesis. To date, only a few regulators have been identified as being involved in the regulation of butenyl-spinosyn production in S. pogona , including the SenX3/RegX3 system, Sp1418, Sp13016, SP_1288 and an AfsR regulatory factor [ 7 11 ]. A better understanding of the regulatory mechanisms of butenyl-spinosyn biosynthesis will provide important insights for strain improvement by metabolic engineering.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, low phosphate levels has been shown to promote the transition phase to aerial mycelium generation ( Tenconi et al, 2012 )and the biosynthesis of secondary metabolites ( Rodriguez-Garcia et al, 2007 ). Recently, Rang et al (2020) found that the growth of S. pogona and the biosynthesis of butenyl-spinosyn were inhibited to a certain extent with the an increase in phosphate levels in the culture medium. There results suggested that phosphorus, as an essential element for organisms, plays a key role in regulating the growth and the biosynthesis of secondary metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…Song, et al used RedEx technology to replace different modules based on the gene cluster of spinosyn and performed heterologous expression in Streptomyces albicans , successfully synthesizing butenyl-spinosyn [ 20 ]. In addition, the concentrations of inorganic salts, such as phosphate and iron salt necessary for microorganisms in culture medium affected the growth and secondary metabolism in Streptomyces [ 21 23 ].…”
Section: Introductionmentioning
confidence: 99%